Electronic band structure and magnetic susceptibility of Ge₁₋xSix solid solutions - Deibuk, V.G.; Shakhovtsova, S.I.; Shenderovski, V.A.; Tsmots, V.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
The magnetic susceptibility (MS) of single crystal Ge₁-xSix (0 < x < 0.1) solid solutions was investigated. Considerable anomalous MS behavior was found. Theoretical estimations of paramagnetic and diamagnetic parts were made. Reconstruction of the band structure of these alloys results in peculiarities of MS as a function of the composition.